Analisis Jabatan dan Analisis Pekerjaan - Prabowo, Budi; Sinaga, Dilan Serviako; Denita, Sabrina Putri; P., Nasywa Salsabila; Putra, Muhammad Apriyo (As-Syirkah: Islamic Economic & Financial Journal, 2024)
The human resource capacity of an organization is its main capital, and its success is directly related to this capital. To achieve the goal of increasing work effectiveness, all employees need to receive continuous training to develop their professional abilities and capacities, as well as inspire them to work harder and more diligently. Implementing comprehensive and systematic supervision and initiatives to improve work discipline internationally can help businesses achieve employee work efficiency while improving overall service quality. Qualitative research with an emphasis on descriptive analysis was used. Methods of solving this problem have been investigated and the results are presented. When looking to fill a specific role in a business, a job analysis is essential. To explain certain social phenomena, researchers analyze and evaluate data in an effort to answer research questions. Job descriptions and job analyzes are the end product of an organization's efforts to identify the skills and experience that an ideal candidate must possess to be successful in a particular role. Employee performance is greatly influenced by analyzing every aspect of the job. Companies should conduct job analyzes to assign employees based on their skills, which will result in more efficient operations and more active competition among employees.